Deployment of biologging tags on free swimming large whales using uncrewed aerial systems. Issue 4 (19th April 2023) - Wiley, David N.; Zadra, Christopher J.; Friedlaender, Ari S.; Parks, Susan E.; Pensarosa, Alicia; Rogan, Andy; Alex Shorter, K.; Urbán, Jorge; Kerr, Iain
Abstract : Suction-cup-attached biologging tags have led to major advances in our understanding of large whale behaviour. Getting close enough to a whale at sea to safely attach a tag is a major limiting factor when deploying these systems. Here we present an uncrewed aerial system (UAS)-based tagging technique for free-swimming large whales and provide data on efficacy from field testing on blue ( Balaenoptera musculus ) and fin ( B. physalus ) whales. Rapid transit speed and the bird's-eye view of the animal during UAS tagging contributed to the technique's success. During 8 days of field testing, we had 29 occasions when a focal animal was identified for attempted tagging and tags were successfully attached 21 times. The technique was efficient, with mean flight time of 2 min 45 s from launch to deployment and a mean distance of 490 m from the launch vessel to tagged animal, reducing potential adverse effects resulting from close approaches for tagging. These data indicate that UAS are capable of attaching biologging tags to free-swimming large whales quickly and from large distances, potentially increasing success rates, decreasing attempt times, and reducing animal disruption during tagging.